Analysis of the Effect of Up Selling and Cross Selling Sales Methods on the Brand Image of KFX UB Jaya I Pharmacy and its Impact on Purchasing Decisions - Indra, Hivzil; Saragi, Sahat; Putriana, Lies (GoAcademica Research & Publishing, 2024)
Data on drug sales reports at KFX UB Jaya I Pharmacy in the last 3 years shows a decrease in the Non-Prescription Drug category. One of the strategies to increase sales pursued by KFX UB Jaya I Pharmacy is by implementing the Up-selling and Cross-selling methods. The purpose of this study is to determine the effect of Up-selling and Cross-selling sales techniques for non-prescription drugs on consumer purchasing decisions, and how it impacts the brand image of KFX UB Jaya I. This study uses quantitative research methods and descriptive design with an approach using questionnaires as research instruments. Determination of the research sample using the random sampling method with the SEM model, which amounted to 134 customers of the KFX UB Jaya I Pharmacy as a community pharmacy. The results showed that there was a positive influence between Up-selling on brand image (t: 4.373 & p: 0.000) and on purchasing decisions (t: 2.464 & p: 0.014). Meanwhile, the Cross-selling sales method has a significant effect on brand image (t: 5.359 & p: 0.000) and on purchasing decisions (t: 3.561 & p: 0.000). The results also show that brand image has a significant effect on purchasing decisions (t: 5,763 & p: 0.000). Brand image can mediate the influence between Up-selling on purchasing decisions (t: 3,563 & p: 0.000) and between Cross-selling on purchasing decisions (t: 3,862 & p: 0.000). Based on the results obtained from research and literature studies, up-selling and cross-selling sales methods for non-prescription drugs have an effect on the brand image of the KFX UB Jaya I pharmacy which also has a significant impact on purchasing decisions.